Estudio de factibilidad para la creación de un local de comidas rápidas en cantón La Maná, provincia de Cotopaxi año 2023. - Briones Cedeño, Selene Lizbeth (2023)
The present research work entitled, feasibility study for the implementation of a fast food restaurant in La Maná canton during the year 2023, was carried out under a quantitative approach, descriptive type, supported by field research with which the collection of documentary information with which the theoretical framework. Among the methods, we have analysis and synthesis, the statistical, inductive and deductive methods that served to generate the conclusions of the project with the information collected, as the population consisted of the families of La Maná canton, according to data from INEC and the sample was 374 families to whom was applied the questionnaire, the same that consisted of elaborated questions, in addition for the development of the product offer we went to the existing fast food outlets for the collection of information. Among the results was found that the main costs and expenses generated within the production process of fast food, investment in fixed assets which ranges from $4,155.00, the incorporation expenses amounting to $1,550.00, the working capital for the first month were $5,322.61, giving an initial investment of $10,947.61, the values in raw material annually amount to $26,299.20, as for the estimate of salaries for the first year $30,508.40 is canceled. The income represented about $103,740.00 product of the amount sold annually, and the net profit was $27,336.80. Within the financial analysis based on the financial application indicators such as NPV and IRR, the Van is $111.049, 58, which indicates its feasibility. When calculating the Internal Rate of Return, based on cash flows and NPV, an IRR of 34, 41% is obtained, which is the percentage of the investment that will recover during each year of operation, which shows that the project is feasible. The CBR is 1.87, which indicates that the project is very profitable. The break-even point in units is reached at 13,441 and in dollars when selling at $40,324.07.